Mythological Dimensions In The Selected Works Of Anita Nair, Anuja Chandramouli And Sally Kempton (Journal of Namibian Studies : History Politics Culture, 2024)
Human beings, the founders of different religions and sects, hold theirrespective views, beliefs and value systems. Rites, Beliefs, rituals and religious practices differ in different religions, faiths and sects. Moreover, various religions relate spiritual entities to different mythologies. Indian mythology forms the backbone of Indian Writings in English. The present paper makes an attempt to study Hindu religious practices that project various incarnations of ‘Goddess Shakti’. Representation of these incarnations and their worship in a mythological framework in the works of writers such as Anita Nair, Anuja Chandramouli and Sally Kempton has been looked into.